Multiple origins of congested inflorescences in Cyperus S.S. (Cyperaceae): Developmental and structural evidence - Guarise, Nicolas Javier (2012)
Premise of the study: The understanding of homoplasic structures becomes more relevant when they are complex and define large angiosperm taxa. Inflorescence architecture usually fulfills both features, as happens with Cyperus, a genus with two taxonomical subdivisions characterized either by alternative expressions of Kranz anatomy (C3or C4) or inflorescence shape (condensed or lax). Those subdivisions are not completely congruent because at least one of these presumed characters has evolved several times. We focused a SEM study on the inflorescence development in species with condensed inflorescences and different photosynthetic anatomy to test the possibility that condensed inflorescences of subgen. Anosporum (C3anatomy) have evolved independently from those of subgen. Cyperus (C4anatomy). Methods: Freshly collected inflorescences of C. entrerianus, C. eragrostis, C. oxylepis, and C. incomtus were studied using stereoscopic and scanning electron microscopy. Key results: Condensed inflorescences of Cyperus species with C3and C4anatomy had differences in structure and development: (1) mature structure, (2) position of second-order branching initiation in the first developmental stage of the inflorescence, (3) main axis development and elongation, and branching development, (4) types of ramifications, (5) phyllotaxis and symmetry. Conclusions: Results support multiple origins of condensed inflorescences in Cyperus, based especially on differences in timing during development and elongation of the main axis and branches, branching pattern and phyllotaxis. Structure and development may be the key to using inflorescence morphology as an external feature to distinguish large natural groups within Cyperus based on vegetative anatomy. © 2012 Botanical Society of America.